2016
DOI: 10.1155/2016/1459790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omega-3 Fatty Acid in Nonalcoholic Fatty Liver Disease: A Meta-Analysis

Abstract: A meta-analysis was conducted to assess the effect of omega-3 fatty acid supplementation (n-3 PUFAs) in lowering liver fat, liver enzyme (alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutamyltransferase (GGT) levels), and blood lipids (triglyceride (TG), total cholesterol (TC), high density lipoprotein (HDL), and low density lipoprotein (LDL)) in patients with nonalcoholic fatty liver disease (NAFLD) or nonalcoholic steatohepatitis (NASH). Methods. MEDLINE/PubMed, EMBASE, the Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 47 publications
8
80
2
2
Order By: Relevance
“…However, we also recommend including obeticholic acid in their guidelines considering the results from this meta-analysis. Lu et al 144 and He et al 145 observed beneficial effects in terms of reduction in the aminotransferase levels with PUFA and suggested as a treatment option for NAFLD from their meta-analysis. Although our results are in corroboration with these meta-analyses, we did not observe any significant changes in either the response rate or NAS.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also recommend including obeticholic acid in their guidelines considering the results from this meta-analysis. Lu et al 144 and He et al 145 observed beneficial effects in terms of reduction in the aminotransferase levels with PUFA and suggested as a treatment option for NAFLD from their meta-analysis. Although our results are in corroboration with these meta-analyses, we did not observe any significant changes in either the response rate or NAS.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that hepatic content of triglycerides was decreased by the downregulation of hepatic triglyceride synthesis and the upregulation of hepatic triglyceride oxidation in rats fed n-3 PUFA [34]. In addition, meta-analysis of randomized controlled trials showed that n-3 PUFA supplementation improved liver steatosis and liver function in patients with NAFLD [13,14,15]. This study also showed that erythrocyte levels of n-3 PUFA, 20:5n3, and 22:5n3 and the Omega-3 Index were lower in patients with NAFLD and negatively associated with the risk of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Elizondo et al [12] showed that the erythrocyte level of n-3 PUFA, a marker for fish intake, was significantly lower in patients with NAFLD than healthy controls. Recent meta-analysis of randomized controlled trials consistently reported that n-3 PUFA supplementation could be a practical and effective treatment for NAFLD [13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, epidemiological studies implicated a lower consumption of omega‐3 PUFA and a higher n‐6/n‐3 ratio among NAFLD and NASH patients compared to controls . In a meta‐analysis of 10 RCTs, omega‐3 PUFA treatment was beneficial in terms of decreased amount of liver fat observed on US and improved gamma‐glutamyl transferase (GGT), but it was not significantly efficient in reduction of ALT and aspartate aminotransferase (AST) . Recent RCTs assessed the effect on NASH and fibrosis, yielding positive results with regard to liver fat reduction and disappointing results with regard to NASH or fibrosis .…”
Section: The Association Between Individual Components Of the MD And mentioning
confidence: 99%